The Necessary Training Needs for UNRWA Schools Teachers in the Light of E- Learning from the Principals’ Points of View - Marshood, Jamal Mohammad; Ibrahim, Asma' Osamah; Ghawadrah, Suar Maezuz; Salih, Raghad Hasan; Najaar, Bayan Adil (Journal of Educational and Psychological Sciences, 2022)
The purpose of the present study is to know the necessary training needs for UNRWA school teachers in the light of e- learning from the principals’ points of view. The researcher used a descriptive approach, The tool of the study was a questionnaire which consisted of (42) items distributed among four fields (computer driving, internet leadership, e- learning culture, educational software and multimedia), the sample of the study consisted of (96 School Principal and Assistant School Principal) at the scholastic year 2020/2021, The statistical analyses were carried out by using SPSS, the researcher used (T- Test، One Way Anova) to answer the study questions. The study found out that the total degree of training needs necessary for UNRWA school teachers in light of e- learning from the principals’ points of view got a total average of ((3.33 out of 5), which meant it had a (moderate) degree, Meanwhile, at the fields level, the computer driving field got the highest average (3.70) with a (high) degree, then the Internet leadership field got an average of (3.46) with a (high) degree, then the e- learning culture field got an average of (3.30) with a (medium) degree, and finally the Educational software and multimedia field got an average of (2.81) a (medium) degree, there weren’t significant differences attributed to gender and educational area variables on all fields, and there were significant differences attributed to qualifications variable in favor of more than bachelor’s degree.